New Products from Surimi -A Report of Workshop Experience with Fishermen in The Coastal Region of Rio De Janeiro - Joyce Tarsia Garcia Cafiero; Ana Lucia do Amaral Vendramini; Ítalo de Paula Casemiro (Universidade Estadual de Alagoas, 2021)
Fishing is a subsistence activity practiced by several communities in the coastal region of the State of Rio de Janeiro. The present study presents the experience report of an activity of transfer of technology for the production of products from fish (technique of preparing surimi), through workshops with fishermen from communities in the State of Rio de Janeiro. Workshops are presented as an interesting resource to promote interaction and at the same time the exchange of knowledge between academia and society. The workshops were held in fishing communities in the municipalities of Mangaratiba, Arraial do Cabo and Cabo Frio. Among the activities, interviews were conducted to collect social data from the participating groups, holding fish processing workshops, assessing the sensory acceptance of the products generated and the intention of producing / selling the products. During the workshops for the processing of surimi and the production of pasta made from this product, it was identified that fish is not the most consumed protein in the households of the interviewees. the development of new products and the full use of fish. The production processes were carried out in public food systems (schools and community production) with easily accessible equipment, however it was reported that the preparation of surimi is laborious and time consuming, but the final result is satisfactory and positively impacting. The research allowed the actors involved to get to know new technologies, giving them the perspective of managing new ventures and creating new products.